Walter Kaufmann and the Winnipeg Ballet: A Fruitful Collaboration Soon Forgotten - Gaub, Albrecht (Les Cahiers de la Société québécoise de recherche en musique, 2013)
The early years of the Royal Winnipeg Ballet (RWB), the era of its founding director Gweneth Lloyd (1901–1993), remain a “dark age” because in 1954, all possessions of the company perished in a fire. Earlier attempts at writing the history of this institution, such as Max Wyman’s book The Royal Winnipeg Ballet: The First Forty Years (Toronto, Doubleday, 1978) and Jeff McKay and Patti Ross Milne’s documentary film 40 Years of One Night Stands (2008), suffer from a general neglect of the music used by the company. The RWB mounted several ballets to original music, typically by Canadian composers. Walter Kaufmann (1907–1984), a German-Jewish composer exiled after 1934, living in Canada from 1947, and appointed conductor of the Winnipeg Symphony Orchestra in 1948, received commissions for Visages, an abstract ballet for the company’s tenth anniversary in January 1949, and The Rose and the Ring, a “children’s Xmas ballet” (RWB), first performed in December of the same year. Creation, aesthetics, and reception of these ballets are evaluated on the basis of Kaufmann’s surviving autograph scores at Indiana University in Bloomington and of contemporaneous documents, especially press reviews and, in the case of Visages, a documentary film by the National Film Board of Canada, Ballet Festival (1949). Visages was immediately hailed as a major artistic achievement and remained a staple of the RWB’s repertory until the 1954 fire. The RWB showcased Visages at the Canadian Ballet Festivals in Toronto (1949) and Montréal (1950), drawing praise from renowned critic Anatole Chujoy, and regularly presented it on its tours, including one to Washington, D.C. (1954). Referring to Anna Blewchamp’s reconstruction to Lloyd’s ballet The Wise Virgins, which was also lost in the 1954 fire, chances for a revival of Visages are assessed.